2021
DOI: 10.1155/2021/1562605
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Contact Low-Frequency Ultrasound and Pulse Lavage Eradicates Biofilms on Implant Materials In Vitro

Abstract: Pulse lavage (PL) debridement and ultrasound are both known to be the treatment of biofilm-related periprosthetic joint infection (PJI). However, the efficacy of these in combination is unknown in eradicating biofilm from the orthopaedic metal implant surface. This study was conducted to understand the efficacy of PL and ultrasound in combination in eradicating bacterial biofilms on titanium alloy in vitro. Biofilms of Staphylococcus aureus strains were grown on titanium alloy coupons for 24 h. Then, the coupo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…show that the combination of PL and sonication is able to completely dislodge the biofilm. 24,31 Moreover, the values of absorbance that we obtained for PL + Sonication groups and PUS + Sonication groups of each material are not statistically different, therefore, the sonication used in our study is able to dislodge the biofilm regardless which lavage/debridement has been used.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…show that the combination of PL and sonication is able to completely dislodge the biofilm. 24,31 Moreover, the values of absorbance that we obtained for PL + Sonication groups and PUS + Sonication groups of each material are not statistically different, therefore, the sonication used in our study is able to dislodge the biofilm regardless which lavage/debridement has been used.…”
Section: Discussionmentioning
confidence: 64%
“…Our results showed PL had approximately a two-log reduction of CFU/mL in all materials compared to the control and this is consistent with previous studies that reported the same reduction. 21,23,24 These studies assess that PL removes a large part of biofilm, but some authors have pointed out that residual bacteria on disks after PL are sufficient to restore a biofilm. 39 Although it is not known which is the minimum bacterial density for an implant to become infected, it is crucial to reduce as much as possible this value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations